Six-Minute Walk Test In Young Healthy University Players: Gender Difference And Anthropometric Correlates (International Journal of Environmental Sciences, 2025)
Distance covered (6MWD, m) in the six-minute walk test (6MWT) is a valid and simple aerobic endurance test. However, data is scarce in young, healthy Indian university players. Hence, the study was conducted to evaluate gender differences and anthropometric correlates of 6MWD.Forty-four healthy university players (31 males) volunteered. Height (HT, cm), weight (WT, kg), bioelectric impedance-based body fat percentage (BF), waist circumference (WC, cm), hip circumference (HC, cm), waist-hip ratio (WHR), waist-height ratio (WHtR), and resting heart rate (rHR, bpm) were the studied parameters. The 6MWT was conducted as per the American Thoracic Society’s guidelines.Males had significantly higher HT, WT, and 6MWD (730.91 ± 64.21 m vs. 680.82 ± 75.59 m) but lower WHtR and BF than females. The cut-offs for lower and higher 6MWD for males (20–27 years) and females (21–24 years) were: 690.15 m, 776.18 m and 620.97 m, 736.85 m, respectively. Gender differences in 6MWD might be related to differences in HT, WHtR, and BF.There was a significant positive correlation of 6MWD with HT (6MWD = 4.899 HT – 109.882, r² = .182, SEE = 59.055) in males, and a negative correlation with WC (6MWD = –10.705 WC + 1500.573, r² = .540, SEE = 53.5597), WHtR (6MWD = –1173.879 WHtR + 1261.002, r² = .344, SEE = 63.939), and age (6MWD = –59.485 Age + 2021.524, r² = .476, SEE = 57.127) in females.Controlling for gender (1 = male, 2 = female), a significant negative correlation of 6MWD was found with BMI, WC, HC, and WHtR. Significant prediction equations generated with the highest adjusted r² (adj. r²) for gender and an anthropometric variable were: 6MWD = –16.934 BMI – 47.334 Gender + 1145.523, adj. r² = .293, SEE = 59.483, 6MWD = –726.651 WHtR – 21.035 Gender + 1082.032, adj. r² = .229, SEE = 62.1296.The results showed not only the anthropometric basis of the gender gap in 6MWD but also the significant correlates and predictors of 6MWD, hinting at the possible role of these easily measurable anthropometric variables in training monitoring and talent identification. The results provide a platform for future well-designed studies to generate normative reference values for 6MWD.